Kualitas Pengungkapan Sustainable Development Goals (SDGs) dan Kinerja Keuangan: Bukti Empiris atas Perusahaan Pertambangan di Indonesia - Nadhila Putri Arifianti; Luky Patricia Widianingsih (AKUNTANSI DEWANTARA, 2022)
This study aims to analyze and examine the effect of the quality of SDGs disclosure in the Sustainability Report on the company's financial performance. The quality of reporting on the SDGs in this study is seen from the presentation of reporting on the company's contribution to the SDGs, whether presented qualitatively or quantitatively. Financial performance is measured using the ratio of Return on Assets (ROA). The population of this study are mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2020 period. This study uses a purposive sampling method with several criteria which then become the sample. Furthermore, for the reporting quality variable using the scoring method. The sample of this study amounted to 18 companies. The result of this study is that the reporting quality of SDGs has no significant effect on ROA. While the size of the company has an influence on ROA